Hot deformation studies of AISI 1035 steel using thermo mechanical simulator. (2020) - Ohdar, R.K.; Equbal, Azhar; Equbal, Md Israr
Abstract: Uni-axial hot compression tests were conducted in the temperature range of 900–1100 °C and strain rate range of 0.2–20 s −1 using thermo-mechanical simulator in order to study the effect of forging conditions viz. temperature and strain rate on flow behaviour of AISI 1035 medium carbon steel. The results indicate that both the parameters have profound effect on flow stress. The curves of true stress strain revealed that flow stress increases with lowering of forging temperature and with an increase in strain rate. At all deformation conditions flow softening phenomena was observed which were reflected by a peak followed by a drop in flow stress with further straining. Flow softening was predominantly due to dynamic recrystallization at lower strain rates of 0.2/s and 2/s. Peak stress shifted towards higher strain with an increase in strain rate at all deformation temperatures. Experimental data were fitted to Arrhenius-type constitutive equations to find material constants and activation energy. The calculated stress values were compared with the measured ones and they showed very good agreement, which confirm that the proposed deformation constitutive equations could predict an accurate and a precise flow stress value for AISI 1035 steel. The microstructures of the deformed specimens under different deformation conditions were analyzed using optical microscopy.